Regressivity in public pension systems: the case of Peru - Valderrama Torres, José Artemio (2024)
We study the role of income-mortality differentials and pension eligibility conditions on the level of regressivity and progressivity of Peru’s public pension system, using administrative records from 1999 to 2018 to do so. We consider the joint effect of insufficient contributions, by which the poorest contribute to the pension system but ultimately do not qualify for pensions because of insufficient contributions, and differing mortality by socioeconomic status in contributing to regressivity of the system. We find that the impact of insufficient contributions is more important than the impact of higher mortality in making the system regressive.